Selection, Optimization and Compensation Strategy and Social Support as a Predictors of Elders Psychological well-being. The Case of West Shewa Zone, Oromia, Ethiopia (Global Journal of Human-Social Science, 2017)
Psychological wellbeing is a crucial concern of the elderly The aim of this study was to examine whether Selection Optimization Compensation strategy and social support is predicting elders psychological well-being or not At the same time patterns of Psychological wellbeing across demographic variables was identified In order to achieve the objective of the study community based descriptive survey design were used Data were collected from arbitrarily selected 393 elders 170 males and 223 females in Western Shewa Town through questionnaire As the result of the study revealed most elders have moderate and below moderate Psychological wellbeing 30 3 49 4 Selection Optimization Compensation strategy 31 6 47 7 and social support 41 5 37 7 respectively Also the result of the study indicated that Psychological well-being was significantly and positively correlated with social support r 977 P 01 SOC r 980 P 01 income r 772 P 01 and educational level r 687 p 0 01 while age were significantly negatively correlated to psychological wellbeing of elderly r - 421 P 01 As of the t-test showed there is significant gender difference between Male mean 136 72 SD 49 29 and female M 92 41 SD 42 83 total 393 t 9 52 P 000 two-tailed P 05 in experiencing Psychological wellbeing On other hand Oneway ANOVA indicated that there is significant psychological well being F 42 451 P 000 difference among elder s age categories young old and old old age elder The Scheffe post hoc tests also showed that there was a significant mean difference between elder s ages categories which implies young elderly had more psychological wellbeing than those were advanced in age To promote psychological wellbeing of elderly it was suggested that responsible organizations should establish different programs and activities that promote psychological well beings of elder
Keywords: social support; psychological well-being; selection; optimization and compensation strategy